2015
DOI: 10.3389/fpls.2015.00927
|View full text |Cite
|
Sign up to set email alerts
|

Role of ethylene in responses of plants to nitrogen availability

Abstract: Ethylene is a plant hormone involved in several physiological processes and regulates the plant development during the whole life. Stressful conditions usually activate ethylene biosynthesis and signaling in plants. The availability of nutrients, shortage or excess, influences plant metabolism and ethylene plays an important role in plant adaptation under suboptimal conditions. Among the plant nutrients, the nitrogen (N) is one the most important mineral element required for plant growth and development. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 183 publications
2
46
1
1
Order By: Relevance
“…A recent publication by Khan et al. () has shown that the PDX1.1 gene is transcriptionally downregulated under conditions of N starvation. Quantitative results related to cultivar Creso in spot 18 were statistically significant in the case of CL and CS, whereas no significant data were reported for spot 19.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication by Khan et al. () has shown that the PDX1.1 gene is transcriptionally downregulated under conditions of N starvation. Quantitative results related to cultivar Creso in spot 18 were statistically significant in the case of CL and CS, whereas no significant data were reported for spot 19.…”
Section: Discussionmentioning
confidence: 99%
“…Under nutritional stress, plants accumulate stress ethylene [24]. The stress generating ethylene, when adjacent to the chloroplast, degrades lipids in the cell membrane and activates chlorophyllase (chlase) gene [25].…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene is a gaseous plant hormone with versatile role in regulating photosynthesis and growth responses under abiotic stress (Wang et al, 2013; Khan and Khan, 2014; Schellingen et al, 2014; Asgher et al, 2015; Thao et al, 2015; Khan et al, 2015c). Fu et al (2014) studied the regulatory interaction between S-assimilation and ethylene for tolerance to arsenic in Arabidopsis Col-0.…”
Section: Introductionmentioning
confidence: 99%